Analysis Of Feasibility Of Agro-Industrial Businesses In Kelurahan Simpang Three Kecamatan Kuantan Tengah Central Kuantan District (Case Study on Abdori's Tofu Agro-Industry) - Agung Seprianto; Meli Sasmi; Mahrani Mahrani (Baselang, 2021)
This research was conducted in Simpang Tiga Subdistrict, Kuantan Tengah Subdistrict, Kuantan Singingi Regency, which was conducted in July to October 2019. The purpose of this study was to determine the financial feasibility analysis (NPV, Net B / C, PR, PBP and BEP) agro-industry know in Simpang Tiga Village, Kuantan Tengah District, Kuantan Singingi Regency. The results of the Feasibility Study of Abdori Tofu Agroindustry Business in Simpang Tiga Village, Kuantan Tengah District based on Net Present Value (NPV), Net B / C Ratio and Profitability Ratio have positive values where the Abdori Tofu Agroindustry is very feasible to run, this can be seen in the Net value The Present Value (NPV) is Rp 3,722,911,109.27, the Net B / C Ratio is 2.03, the Profitability Ratio is 38.73, which moves positively. For Pay Back Period (PBP) of Tofu Abdori Agroindustry at 25 days. Whereas the Break Event Point (BEP) of Abdori Tofu Agroindustry at 1 year 8 months 14 days.